Maintaining skeletal muscle mass: lessons learned from hibernation. Issue 4 (17th January 2014) - Ivakine, Evgueni A.; Cohn, Ronald D.
Abstract : New Findings: What is the topic of this review? This report describes identification and characterization of serum‐ and glucocorticoid‐regulated kinase 1 (SGK1) as a regulator of skeletal muscle mass during hibernation, as well as in physiological and pathophysiological conditions in non‐hibernating species. What advances does it highlight? This is first demonstration that SGK1 plays a crucial role in skeletal muscle homeostasis. Overexpression of SGK1 protects mice from immobilization and starvation‐induced muscle atrophy. Serum‐ and glucocorticoid‐regulated kinase 1 should be considered as a novel therapeutic target to combat loss of muscle mass in multiple conditions. Muscle disuse and starvation are often associated with a catabolic response leading to a dramatic loss of skeletal muscle mass. Hibernating animals represent a unique situation where muscle mass is maintained despite prolonged periods of immobilization and lack of nutrition. We analysed the molecular pathways upregulated during hibernation in an obligate hibernator, the 13‐lined ground squirrel ( Ictidomys tridecemlineatus ). Although Akt has an established role in skeletal muscle maintenance, we found that activated Akt was decreased in skeletal muscle of hibernating squirrels. Another serine–threonine kinase, serum‐ and glucocorticoid‐regulated kinase 1 (SGK1), was upregulated during hibernation and contributed to protection from loss of muscle mass via downregulation of proteolysis and autophagy and via an increase in protein synthesis. We extended our observations to non‐hibernating animals and demonstrated that SGK1‐null mice developed muscle atrophy. These mice displayed an exaggerated response to immobilization and starvation. Furthermore, SGK1 overexpression prevented immobilization‐induced muscle atrophy. Taken together, our results identify SGK1 as a novel therapeutic target to combat skeletal muscle loss in acquired and inherited forms of muscle atrophy.